2004
DOI: 10.1002/jcb.20138
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of platelet‐derived growth factor stimulated migration and proliferation in osteoblastic cells

Abstract: Osteoblastic migration and proliferation in response to growth factors are essential for skeletal development, bone remodeling, and fracture repair, as well as pathologic processes, such as metastasis. We studied migration in response to platelet-derived growth factor (PDGF, 10 ng/ml) in a wounding model. PDGF stimulated a twofold increase in migration of osteoblastic MC3T3-E1 cells and murine calvarial osteoblasts over 24-48 h. PDGF also stimulated a tenfold increase in 3H-thymidine (3H-TdR) incorporation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 52 publications
4
44
0
Order By: Relevance
“…To the best of our knowledge, our study is the first to report this phenomenon in tumor cells. Our conclusion of involvement of both MAPKs in tumor cell line proliferation is also supported by reports of involvement of ERK and JNK in the proliferation of nontumorous EPOdependent erythroid cells (30), as well as in platelet-derived growth factor-induced proliferation of oesteoblastic MC3T3-E1 cells (46). In summary, our present observation shows that AR42J cells express EPOR.…”
Section: Discussionsupporting
confidence: 91%
“…To the best of our knowledge, our study is the first to report this phenomenon in tumor cells. Our conclusion of involvement of both MAPKs in tumor cell line proliferation is also supported by reports of involvement of ERK and JNK in the proliferation of nontumorous EPOdependent erythroid cells (30), as well as in platelet-derived growth factor-induced proliferation of oesteoblastic MC3T3-E1 cells (46). In summary, our present observation shows that AR42J cells express EPOR.…”
Section: Discussionsupporting
confidence: 91%
“…We have noted previously that unlike the case of many other mitogens such as platelet-derived growth factor and fibroblast growth factor-2 (whereby stimulation of DNA synthesis is measurable already after 24 h) (39,40), ϳ48 h are required before the mitogenic action of OGP-(10 -14) becomes traceable (10). We therefore assumed that the OGP-(10 -14)-activated signaling cascade downstream of the MAP kinase involves de novo mRNA and protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 In addition, PDGF accelerated cell proliferation via mitogen-activated protein kinase 8. 23 Previous research has shown a connection between v-raf-leukemia viral oncogene 1 and serum response factor in the PDGF pathway, and these genes regulate cell proliferation. 24,25 Microarray analysis showed that the expression level of these PDGF-related genes were lower in miR-29a liver than in NC miRNA liver (Figure 8a).…”
Section: Controlling Liver Fibrosis Through Preventionmentioning
confidence: 99%